Venous Thromboembolism After Peripherally Inserted Central Catheters Placement in Children With Acute Leukemia: A Single-center Retrospective Cohort Study. Issue 6 (August 2020) - Ren, Yuanyuan; Chang, Lixian; Zhao, Beibei; Zhang, Xiaoyan; Wan, Yang; Zhu, Xiaofan; Zhang, Huimin
Abstract : Objective: To explore the incidence rate and characteristics of symptomatic venous thromboembolism (VTE) after peripherally inserted central catheters (PICC) placement in children with acute leukemia (AL). Methods: The authors performed a retrospective study aiming at children admitted to Pediatric Blood Diseases Center with a new diagnosis of AL and received a PICC insertion, collected the clinical materials of all venous thrombosis cases, and analyzed the incidence rate and characteristics in various types of AL. Results: From September 2007 to December 2018, a total of 2423 patients got PICCs at least once, of whom 29 patients experienced thrombosis events and the overall incidence rate of symptomatic VTE after PICC insertion was 1.2%. Deep venous thrombosis accounted for the majority with 75.9%. Seven cases of cerebral venous sinus thrombosis were documented and they all developed in patients with acute lymphoblastic leukemia (ALL). No pulmonary embolism was detected. Patients with acute myeloid leukemia (AML) had an identical risk of thrombosis to patients with acute lymphoblastic leukemia (ALL) (1.7% vs. 1.09%, P >0.05). All thrombi in patients with AML were located on the upper extremity, whereas in the ALL group about half of the thromboembolism developed in other locations. There were no statistical differences between patients in different clinical trials of the ALL group (0.7% vs. 1.6%, P >0.05). Conclusions: The incidence rates of symptomatic VTE after PICC placement in children with AL in our center were relatively low and acceptable. For patients with AML, PICC placement plays the most important role in venous thrombosis. However, in patients with ALL, the potential risk factors were more complex.